An Assessment Method of Structure Strength Analysis on Full-Scale LNG Independent Type C Tank. (September 2020) - Liu, Ge; Xie, Zheng; An, Qianglin; Pei, Fei
Abstract: The sloshing induced by partial loaded in LNG (Liquified Natural Gas) independent type C tank will threat the structure of tank. The strength check of the tank plays an important role in the design of LNG tank, which can also improve the safety of the cargo containment system. Hence, an assessment method of the structure of LNG independent type C tank is presented, in which the method of one-way fluid-structure interaction is used. Sloshing load is considered with a numerical technique based on CFD theory, which can reduce large computational expense and remain a good accuracy. The dangerous conditions of sloshing pressure are determined by frequency domain analysis of the tank and ship. By computation of sloshing condition of 1000 m 3 fuel bunker vessel, the feasibility of this method is explained and suggestions on structure design of tank is given.